Common Goods and Sustainable Development - Prandecki, Konrad (European Journal of Sustainable Development, 2017)
Common good is a solution that has little meaning in the modern economy. Historical experience shows that, in the past, it has significantly contributed to the stability and development of many local communities. However, it can still be useful. The purpose of this article is to compare the benefits of the common good with the objectives of sustainable development. The common good can be evaluated in two ways, as a product or process. The first of these ways is based on an analysis of the characteristics of the good, and the other one on the processes supporting its creation. Product approach is more common in economic theory, but a process analysis of the common good is more adequate to indicate its significant advantages in the context of sustainable development. The results obtained indicate that the described solution can be successfully applied in the framework of the concept of sustainable development. In most cases, this is due to the integration of the social and economic needs of society. In some cases, environmental aspects can also cause a lot of benefits. The article was written based on critical analysis of available literature. Keywords: Commons, common pool resources, sustainable development